Mortality in biopsy-confirmed nonalcoholic fatty liver disease: results from a nationwide cohort. Issue 7 (9th October 2020) - Simon, Tracey G; Roelstraete, Bjorn; Khalili, Hamed; Hagström, Hannes; Ludvigsson, Jonas F
Abstract : Objective: Population-based data are lacking regarding the risk of overall and cause-specific mortality across the complete histological spectrum of non-alcoholic fatty liver disease (NAFLD). Design: This nationwide, matched cohort study included all individuals in Sweden with biopsy-confirmed NAFLD (1966 to 2017; n=10 568). NAFLD was confirmed histologically from all liver biopsies submitted to Sweden's 28 pathology departments, after excluding other etiologies of liver disease, and further categorised as, simple steatosis, non-fibrotic steatohepatitis (NASH), non-cirrhotic fibrosis and cirrhosis. NAFLD cases were matched to ≤5 general population comparators by age, sex, calendar year and county (n=49 925). Using Cox regression, we estimated multivariable-adjusted HRs (aHRs) and 95% CIs. Results: Over a median of 14.2 years, 4, 338 NAFLD patients died. Compared with controls, NAFLD patients had significantly increased overall mortality (16.9 vs 28.6/1000 PY; difference=11.7/1000 PY; aHR=1.93, 95% CI=1.86 to 2.00). Compared with controls, significant excess mortality risk was observed with simple steatosis (8.3/1000 PY, aHR=1.71, 95% CI=1.64 to 1.79), non-fibrotic NASH (13.4/1000 PY, aHR=2.14, 95% CI=1.93 to 2.38), non-cirrhotic fibrosis (18.4/1000 PY, aHR=2.44, 95% CI=2.22 to 2.69) and cirrhosis (53.6/1000 PY, aHR=3.79, 95% CI=3.34 to 4.30)(ptrend <0.01). This dose-dependent gradient was similar when simple steatosis was the reference (ptrend <0.01). The excess mortality associated with NAFLD was primarily from extrahepatic cancer (4.5/1000 PY, aHR=2.16, 95% CI=2.03 to 2.30), followed by cirrhosis (2.7/1000 PY, aHR=18.15, 95% CI=14.78 to 22.30), cardiovascular disease (1.4/1000 PY, aHR=1.35, 95% CI=1.26 to 1.44) and hepatocellular carcinoma (HCC) (1.2/1000 PY, aHR=11.12, 95% CI=8.65 to 14.30). Conclusion: All NAFLD histological stages were associated with significantly increased overall mortality, and this risk increased progressively with worsening NAFLD histology. Most of this excess mortality was from extrahepatic cancer and cirrhosis, while in contrast, the contributions of cardiovascular disease and HCC were modest.